Playful pictures : art, leisure, and entertainment in the Venetian Renaissance home - Henry, Chriscinda (The Pennsylvania State University Press, 2021)
Introduction : the art of leisure -- Boredom and relief on Carpaccio's Studiolo door -- Pastoral fellowship and the performance of virtuosity -- Theatrical painting from Alla bulesca and Commedia dell'arte -- Ludic art and entertainment in the Venetian Portego -- Epilogue : the carnivalization of Venice.